Editorial - Gallagher, Anne (Anti-Trafficking Review, 2012)
It is my great pleasure and honour to welcome readers to the first issue of the Anti-Trafficking Review. For those of us who have been working on the problem of human trafficking for many years, the emergence of a specialist journal is an important sign of progress – a welcome confirmation that our area of work and study has well and truly moved from the margins to the mainstream of international attention and concern.